Bya-bral Rin-po-che mkhan chen Chos-dbyiṅs-khyab-brdal gyi rnam thar b źugs - Padma-'od-gsal-mtha'-yas 1957- (Si-khroṅ mi rigs dpe skrun khaṅ, 2000)
Biography of Bya-bral Rin-po-che Chos-dbyiṅs-khyab-brdal, b. 1920, of Rñiṅ-ma-pa lama.